PELATIHAN PENGELOLAAN KEUANGAN PADA UMKM DAPROS IBU UDOH DI DESA PONDOK KAHURU, KECAMATAN CIOMAS, KABUPATEN SERANG - Rika Kartika; Raden Irna Afriani; Assyifa Assyifa; Flora Feby Albinarti; Anggi Nur Aisah; Raihan Alhaidar; Azkal Azkiya (Indonesian Collaboration Journal of Community Services, 2023)
Each business unit must have financial transactions that must be recorded. Having neat financial records is a form of financial management. There are many uses of this financial management. One of them is to make it easier for business actors to take policies related to the continuity of the business they are running. Ms. Udoh's Dapros MSME had never previously had financial records, so the community service team was interested in providing education related to recording this financial management. The purpose of this community service activity is to provide education about the importance of financial management and provide direct financial recording training to the Dapros business owner, Mrs. Udoh. The method used in this community service is the counseling method which is carried out directly by visiting the Dapros production business Ibuu Udoh, which is located at Kampung Pancur, Pondok Kahuru Village, Ciomas District, Serang District. After being given education through counseling and financial management training, by practicing financial recording, the owner of the dapros business, namely Ms. Udoh, began to know about how to record finances so that Ms. Udoh could find out how much the sales of dapros were, accounts receivable of dapros, and could even determine profits in selling dapros through education calculating the cost of production to find out the selling price of a decent dapros unit